Origin of dissolved gas (CO2, O2, N2, alkanes) in pore waters of a clay formation in the critical zone (Tégulines Clay, France). (May 2020) - Lerouge, Catherine; Debure, Mathieu; Henry, Benoit; Fernandez, Ana-Maria; Blessing, Michaela; Proust, Eric; Madé, Benoit; Robinet, Jean-Charles
Abstract: Understanding weathering processes in clay formations is an issue of primary importance for the preservation of our natural environment. Reactive-transport modeling used to simulate weathering of clay formations has indicated that reactive gases (CO2 and O2 ) are major parameters in controlling weathering processes. The Lower Cretaceous Tégulines marine-clay formation outcropping in the area of Brienne-le-Chateau (north-eastern France) has been investigated in the context of a sub-surface waste repository. We developed gas monitoring (CO2, O2, N2, alkanes) of core samples from two boreholes that entirely crosscut the Tégulines Clay formation, to define the consequences of weathering and oxidation processes on gases dissolved in pore waters. We discuss amounts of gas and the carbon isotopic composition of CO2 in terms of pore water chemistry including dissolved-inorganic carbon (DIC) and alkalinity, mineral reactivity, organic-matter degradation and oxygen diffusion. Degassing of samples conditioned under He atmosphere provided evidence of very high CO2 production in the soil (0–30 cm), and high CO2 degassing associated with a high oxygen level in the first 2–10 m of the clay. The CO2 degassing increase observed in weathered clay relative to preserved clay resulted from calcite dissolution due to pyrite oxidation and organic matter degradation. The δ 13 C of CO2 indicates that organic matter degradation was a major source of CO2 at shallow depths and down to 10–12 m, which is the maximum depth at which we observed fossil roots. Then the CO2 degassing decreased down to a constant value in preserved clay, where the carbonate system and the mineral assemblage control dissolved carbonates in pore waters. The profile of the δ 13 CCO2 also provides evidence of progressive CO2 diffusion of organic origin from the underlying Greensands aquifer in the lower part of Tégulines Clay up to ~40 m in the AUB230 borehole. As a first step toward understanding interactions between Tégulines Clay and near surface waters or water at the Greensands interface, we developed a reactive-transport model to simulate in one dimension weathering processes under ambient temperature, constrained by geochemical reactions in soil (organic matter degradation) and in the clay (pyrite oxidation and calcite dissolution), exchange, DIC and pore water chemistry. The simulation was carried out for 10 kyrs, assuming that weathering and soil formation began after the last glacial maximum. The DIC profile cannot be simulated without considering evaporation processes in agreement with the isotopic data. This type of approach combining a complete field dataset (reactive-gas concentrations, δ 13 C of CO2, major-ion concentrations, δ 18 O and δD of pore waters) and reactive-transport modeling is necessary for better understanding of chemical weathering processes in the critical zone. Highlights: Reactive gases (CO2, O2 ) and δ 13 C of CO2  boost the understanding of the chemical weathering processes in the critical zone. The simulation of the DIC profile of Tégulines Clay pore waters by reactive transport modelling requires evapotranspiration. CO2 mainly derives from calcite dissolution due to pyrite oxidation and to organic matter degradation. The organic matter degradation is a major source of CO2 down to 10–12 m, maximum depth at which fossil roots are observed.